O impacto da inclusão no mercado de trabalho sobre a vida cotidiana de pessoas com deficiência intelectual: um estudo em uma empresa multinacional - Martins, Magali Wiebusch (Universidade do Vale do Rio dos Sinos, 2014)
The inclusion of people with intellectual disability in the labor market has become more constant and more noticeable nowadays. The quotas law coupled with the social responsibility of employers have intervened for these people, offering them the opportunity to have a dignified job so they can live in equality with the rest of the society. Regarding the inclusion, is relevant to take into account the opinion of the people with intellectual disability, because they are one of the key parts of the process. Therefore, this paper investigates which are the influence of the inclusion in the lives of people with intellectual disability after their insertion in the labor market. The research was established as exploratory, qualitative with semi-open interviews. The respondents were people with intellectual disability, employees at a multinational company, located in Gravataí/RS, the focus of the survey was to collect information of people with intellectual disability specifically at this company. A content analysis of the interviews concluded, among other details, that the intellectual disabled people consider the work as a means of personal development and professional growth. Some of the respondents did not know how to manage money, the fruit of their salary, receiving support from their families for this management, the work for them goes beyond making money, they feel satisfied and happy to be in the labor market and be useful.
Keywords: Deficiência intelectual; Trabalho; Lei de cotas; Responsabilidade Social; Intellectual disability; Responsibility social